Potential Utilization of Wooden Particleboard Patent to Analyze Research and Development Foresight - Sasa Sofyan Munawar; Firman Tri Aji; Tommy Hendrix; Bambang Subiyanto (Masyarakat Peneliti Kayu Indonesia, 2015)
Initiating commodities development from natural resources transforms into primarily issue that preserve many opportunities in utilization of potential and useful diversification model especially wood products. The value of technology analyzes foresight need to be used optimally to seek many opportunities in new variation technology that can implemented into market demand. Now the new technology has pushed into much needed to optimize the amount of raw material that could be processed into new product diversification. One of the problem solution that could comply with analyzing patent database is to find technology from Research and Development (R & D) result to be ready to use, for instance particleboard products as wooden product diversification. This paper discusses on how user could know their development of technology for market orientation through patent portfolio, licensing, status, competitor, innovation and monitoring on emerging market with patent database which has been registered on WIPO fields. Methodology applied in this paper is based on software named Total Patent in order to see more information related to particleboard technology utilization as potential consideration through leading patent-issuing authorities. The aim of paper is to obtain data from patent analysis in particleboard and to find out the development of technology foresight products which have been produced as well as how competitors movement, especially in wood utilization. The conclusion from utilization of R & D on particleboard patent database could be applied in case of developing opportunity in disseminating on industrial and stakeholders which requires impact on newest implementation of technology and level competitiveness in appropriate designation to wooden based products commercialization.